Audit Of Information Technology Governance In The Boss PT. Bahtera Pesat Lintasbuana Using Cobit 2019 - Dewi, Yumi Novita; Nurlaila, Nurlaila (Jurnal CoreIT: Jurnal Hasil Penelitian Ilmu Komputer dan Teknologi Informasi, 2024)
This research, starting from the frame of mind that Audit of Technology Information Governance on Enterprise  information system using COBIT 2019 is an important thing to do now and the future to align information technology investment with Enterprise Goals. COBIT 2019 framework provides realization of the benefits of implementation information systems, optimizing risks and optimizing resources according to Enterprise needs. Design factor of COBIT 2019 can determine the domains that must be assessed for their maturity level, so that companies can find out what needs to be improved in implementing information systems. This research is focus to the EDM02 and APO04 with expected maturity level 5. The EDM02 domain focuses on the process of optimizing the business value contribution of business processes, IT Service and IT assets resulting from investments made by IT in accordance with acceptable cost for the Enterprise. APO04 domain, it aims to organize and manage innovation by increasing operational efficiency in companies with the latest technology.